Ultrasound-Assisted Deep Eutectic Solvent Extraction of Antioxidant and Anti-Colorectal Cancer Proteins from Spirulina Biomass: Process Intensification, Characterization, and Bioactivity Evaluation - May Thu Zin; Thida Kaewkod; Supakit Chaipoot; Gochakorn Kanthakat; Yan-Yu Chen; Benjamas Cheirsilp; Sirasit Srinuanpan (Antioxidants)
Spirulina, a cyanobacterial biomass, is renowned for its high protein content and bioactive compounds, making it a promising candidate for health-promoting applications. This study explores the ultrasound-assisted deep eutectic solvent (DES) extraction technique for isolating antioxidants and anticancer proteins from Spirulina biomass, aiming to enhance extraction efficiency and preserve protein bioactivity. The extraction process was optimized using response surface methodology (RSM), varying parameters such as biomass concentration, sonication amplitude, and extraction duration. The optimized extraction conditions—5% biomass concentration, 40% sonication amplitude, and 22-minute extraction—achieved a high protein yield of 80.62%, with a protein concentration of 442.88 mg/g extract and an essential amino acid content of 39.91%. The extracted proteins exhibited remarkable bioactivity, including strong antioxidant properties, with 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity of 0.25 mg GAE/g, 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) radical scavenging activity of 0.58 mg TE/g, and ferric reducing antioxidant power (PFRAP) of 9.63 mg gallic acid equivalent (GAE)/g. Additionally, the protein extract displayed selective cytotoxicity against colorectal cancer cell lines, with half-maximal inhibitory concentration (IC50) values of 10.25 mg/mL for Caco-2 and 15.40 mg/mL for HT-29 cells, while maintaining low toxicity towards normal Vero cells. Apoptosis rates of 70.43% in Caco-2 and 51.33% in HT-29 cells further confirm the anticancer potential of the extract. The functional properties of the extracted protein, including high foaming capacity (100%), emulsifying capacity (94.05%), and digestibility (85.77%), underscore its potential for diverse applications in food, pharmaceutical, and nutraceutical industries. This eco-friendly and efficient extraction approach aligns with sustainable development goals and offers a viable strategy for harnessing Spirulina’s bioactive potential.